Organizing and Managing Your Research: A Pratical Guide for Postgraduates - Renata Phelps, Kath Fisher, Allan Ellis (Sage, 2007)
It focuses on strategies, skills and systems that increase the efficiency and effectiveness of research practice across all disciplines